TRANSFORMATION OF RICINOLEIC OF CASTOR OIL INTO LINOLEIC (OMEGA-6) AND CONJUGATED LINOLEIC ACID BY DEHYDRATION - Marham Sitorus; S. Ibrahim; H. Nurdin; D. Darwis (Indonesian Journal of Chemistry, 2009)
The ricinoleic of Castor Oil was dehydrated by various dehydrator agent (P2O5, K2CO3, H3PO4, NaHSO4, Al2O3, molecular sieve and activated bentonite at 450 °C - HCl) on the same condition (150 °C, mol ratio 1:1 and 2 hours ). The compositions of Refined Ricinus Castor Oil as starting material were : 0.92% palmitic , 5.56% linoleic , 4.07% octadecanoic , 1.22% stearic and 85.06% ricinoleic. The spesific wave number of IR was bandwith 3411 cm-1 caused of hydroxyl (-OH) group of ricinoleic at C-12 as main component. The product was Dehydrated Castor Oil (DCO) mixed of linoleic (omega 6) [C18 : 2 (9,12)] and Conjugated Linoleic Acid (CLA) [C18: 2 (9,11)]. The best dehydrator was P2O5 based on three parameters were : Free Fatty Acid (FFA) nearly the same (1.855% of Castor oil and 2.139% of DCO), the most increased of Iodium value (49.860 mg/g of Castor oil in to 63.090 mg/g of DCO), and the most decresed of hydroxyl number (28.27 mg of Castor oil in to 17.75 mg/g of DCO). To optimized the dehydration was done by various number of P2O5 (3g, 5g and 7g), tempereture (room, 100 °C and 150 °C) and time (2h, 2.5h, 3h, and 3.5h). The optimal conditon of dehydration was not found yet. Some of sugestted or idea for dehydration were: dehydration must be done by base or netral, non oxydator dehydrator, mol ratio 1:1, temperature (100-150 °C) and 2-3.5 h. Based on GC-MS the best DCO (7g P2O5, 150 °C and 3.5 h) were showed that the decrease of ricinoleic 14.13% (85.08% of Castor Oil in to 70.93% of DCO), increased linoleic 2.09% (5.56 of Castor oil in to 7.65% of DCO) and conducted of 9.09% CLA. Some new peaks between linoleic and ricinoleic are maybe isomer's of linoleic and CLA. The wave number of cunjugated alkene (C=C) (1666.3 cm-1) of IR spectra of DCO together with GC-MS chromatogram's to indicated that linoleic and CLA were conducted.